2020
DOI: 10.1021/jacs.0c08928
|View full text |Cite
|
Sign up to set email alerts
|

Phosphine-Catalyzed Intermolecular Acylfluorination of Alkynes via a P(V) Intermediate

Abstract: We report on the phosphine-catalyzed intermolecular carbofluorination of alkynes using acyl fluorides as fluorinating reagents. This reaction promises to be a useful method for the synthesis of highly substituted monofluoroalkene derivatives, since acyl fluorides can be easily prepared from the corresponding carboxylic acid derivatives and the reaction proceeds under ambient conditions without the need for a transition-metal catalyst. Experimental and computational studies indicate that a five-coordinated fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 49 publications
0
39
0
Order By: Relevance
“…In 2020, they achieved an unprecedented phosphinecatalyzed carbofluorination of alkynes, in which acyl fluorides served as acylating and fluorinating reagents to construct a series of alkenyl fluorides in the excellent yields with great functional-group tolerance (Scheme 50(a)). 96 A series of subsequent mechanistic studies and DFT calculations revealed that an unprecedented ligand coupling on phosphine constructs the C-F bond according to the mechanism shown in Scheme 50 (b) Recently, the same research group developed a novel PCy3catalyzed three-component coupling reaction of acyl fluorides, silyl enol ethers, and alkynes based on previous research. This strategy provides for the synthesis of a variety of 1,3-dienes with good substrate scope and high yields (Scheme 50(c)).…”
Section: Phosphine-catalyzed Indirect Activation Of the C-f Bond Of A...mentioning
confidence: 99%
“…In 2020, they achieved an unprecedented phosphinecatalyzed carbofluorination of alkynes, in which acyl fluorides served as acylating and fluorinating reagents to construct a series of alkenyl fluorides in the excellent yields with great functional-group tolerance (Scheme 50(a)). 96 A series of subsequent mechanistic studies and DFT calculations revealed that an unprecedented ligand coupling on phosphine constructs the C-F bond according to the mechanism shown in Scheme 50 (b) Recently, the same research group developed a novel PCy3catalyzed three-component coupling reaction of acyl fluorides, silyl enol ethers, and alkynes based on previous research. This strategy provides for the synthesis of a variety of 1,3-dienes with good substrate scope and high yields (Scheme 50(c)).…”
Section: Phosphine-catalyzed Indirect Activation Of the C-f Bond Of A...mentioning
confidence: 99%
“…In analogy to previous protocols which utilized i Bu 2 AlH or LiGaH 4 (vide supra), Weaver and co-workers [62] reported the HDF of perfluoroarenes with NaBH 4 (Scheme 20). The advantage of this reaction is that it is compatible with both EDG and EWG substituted substrates (103)(104)(105)(106)(107)(108)(109)(110)(111)(112)(113)(114). Specifically, the use of NaBH 4 rather than more potent reductant LiAlH 4 allowed for the incorporation of ester ( 103) and amide (104).…”
Section: Other Electrophilesmentioning
confidence: 99%
“…Interestingly, Tobisu's group [110] reported a phosphinecatalyzed intermolecular acylfluorination of alkynes using acyl fluorides as the fluorinating reagents (Scheme 40). Halogen groups (207) were compatible in the reactions.…”
Section: Vinylic and Aliphatic C-f Bond Cleavagementioning
confidence: 99%
“…In addition, BF 3 ·Et 2 O and Ph 3 CBF 4 could be used as Lewis acids and fluoride sources to react with enynols to afford tetrasubstituted monofluoroalkenes via formation of allylic carbocation intermediates. Recently, Tobisu and co-workers reported the organophosphine-catalyzed intermolecular carbofluorination of alkynes to produce tetrasubstituted monofluoroalkene derivatives with a low E/Z ratio (Scheme b) . However, this reaction sequence typically involves the consumption of expensive transition-metal catalysts and corrosive/toxic reagents and often results in low regioselectivities.…”
mentioning
confidence: 99%
“…Recently, Tobisu and co-workers reported the organophosphinecatalyzed intermolecular carbofluorination of alkynes to produce tetrasubstituted monofluoroalkene derivatives with a low E/Z ratio (Scheme 1b). 14 However, this reaction sequence typically involves the consumption of expensive transitionmetal catalysts and corrosive/toxic reagents and often results in low regioselectivities. Thus, the development of a simple protocol for the direct access to monofluoroalkenes with suitable regioselectivity control has attracted significant attention in the scientific community.…”
mentioning
confidence: 99%